Efeito antitumoral de um inibidor de PLA2 de Crotalus durissus collilineatus (γCdcPLI) pela modulação da via PI3K/Akt em células de câncer de mama - Gimenes, Sarah Natalie Cirilo (2017)
Phospholipases A2 (PLA2s) overexpression is closely associated with the malignant potential of breast cancers. Here, we showed for the first time the antitumoral effects of γCdcPLI, a PLA2 inhibitor from Crotalus durissus collilineatus via PI3K/Akt pathway on MDA-MB-231 cell. Firstly, γCdcPLI was more cytotoxic to MDA-MB-231 breast cancer cells than other cell lines (MCF-7, HeLa, PC3 and A549) and did not affect the viability of non-tumorigenic breast cell (MCF 10A). In addition, γCdcPLI induced modulation of important mediators of apoptosis pathways such as p53, MAPK-ERK, BIRC5 and MDM2. γCdcPLI decreased MDA-MB-231 adhesion, migration and invasion. Interestingly, the γCdcPLI also inhibited the adhesion and migration of endothelial cells and blocked angiogenesis by inhibiting tube formation by HUVECs in vitro and sprouting elongation on aortic ring assay ex vivo. Moreover, γCdcPLI reduced the production of vascular endothelial growth factor (VEGF). γCdcPLI was also able to decrease PGE2 levels in MDA-MB-231 and inhibited gene and protein expression of the PI3K/Akt pathway. Furthermore, γCdcPLI inhibited the proinflammatory effects of BnSP-7, a PLA2 Bothrops pauloensis of snake venom. Thus the effects of γCdcPLI in PI3K / AKT pathway can be correlated to a possible interaction between the inhibitor and endogenous PLA2s. Thus, we concluded that γCdcPLI showed in vitro antitumoral, antimestatatic and anti-angiogenic potential effects and could be an attractive approach for futures studies in cancer therapy.